Anticipating Groundwater Depletion for Water Scarcity Alleviation through Advanced Deep Learning Models - K, Abrar Ahmed; Z, Inamul Hussain R; Sajid, Md; B, Rahul (IRO Journal on Sustainable Wireless Systems, 2024)
Amidst the challenges posed by climate change, population growth, and pollution, global water availability is diminishing, resulting in critical water shortages. This research proposes a water availability analysis system to tackle the escalating issue exacerbated by urbanization and unsustainable water practices. Conventional methods prove inefficient, prompting the adoption of differentiated analysis through remote sensing and high-resolution mapping for real-time monitoring. The study aims to make a substantial contribution to global water security by providing precise solutions for identifying, managing, and distributing water resources effectively.